2021
DOI: 10.1177/1362168821990968
|View full text |Cite
|
Sign up to set email alerts
|

On the acquisition of complex classifier constructions by L2 learners of a sign language

Abstract: Sign language learners with a spoken language background face the challenge of acquiring a second language in a different modality. In the course of this endeavor, one of the modality-specific phenomena they encounter is the use of classifier predicates, also known as depicting signs. Classifier predicates contain a meaningful hand configuration that refers to an entity, denoting a salient characteristic of this entity (Zwitserlood, 2003). The use of a classifier predicate allows the signer to indicate the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In her contribution to this Special Issue, Boers‐Visker (2023) analyzed plurality production in NGT by hearing learners. Plurality in NGT is expressed in classifier predicates by topographical distribution of noun signs, whereby noun signs are repeated across the signing space, and numeral incorporation, whereby nouns are modified for referent number.…”
Section: Typical Structures Of Sign Languages and How They Are Acquiredmentioning
confidence: 99%
See 2 more Smart Citations
“…In her contribution to this Special Issue, Boers‐Visker (2023) analyzed plurality production in NGT by hearing learners. Plurality in NGT is expressed in classifier predicates by topographical distribution of noun signs, whereby noun signs are repeated across the signing space, and numeral incorporation, whereby nouns are modified for referent number.…”
Section: Typical Structures Of Sign Languages and How They Are Acquiredmentioning
confidence: 99%
“…Plurality in NGT is expressed in classifier predicates by topographical distribution of noun signs, whereby noun signs are repeated across the signing space, and numeral incorporation, whereby nouns are modified for referent number. Boers‐Visker (2023) found that the learners used lexical signs to express numbers (i.e., pluralization) and nouns. Numeral incorporation for pluralization was the most difficult for the learners to produce correctly.…”
Section: Typical Structures Of Sign Languages and How They Are Acquiredmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, their error patterns, especially in the acquisition of CCs, exhibit similarities to those of child learners. Boers-Visker (2021) looked at two-handed CCs in 14 M2L2 learners of NGT and found that learners produced omission errors well into the second year of their studies. In contrast to L1 learners, however, they sometimes self-corrected their productions, adding in the Ground on the non-dominant hand while holding the dominant hand in place.…”
Section: Acquisition Of Classifier Constructionsmentioning
confidence: 99%
“… Ferrara and Nilsson (2017) report that NTS learners (approximately 1.5 years of study) sometimes crossed their arms in depicting an entity’s movement, misjudging the hands’ distance from each other; they would place entities higher in signing space than others that were at the same height in real space. Boers-Visker (2021) noted that learners of NGT had similar difficulties judging the size of the available space and would sometimes have the hands (almost) touching although the objects they represented further apart, or the hands would run out of signing space (e.g., colliding with the torso). Again, the problem may be both cognitive and motoric, requiring the correct estimation of how much space is needed for a given representation and how the two hands need to be positioned toward each other in order to complete their movement unimpeded.…”
Section: Acquisition Of Classifier Constructionsmentioning
confidence: 99%